Editorial - Ryan, Stephen; Mercer, Sarah (Studies in Second Language Learning and Teaching, 2013)
Much of the foreign language learning experience appears to involve the imagination: imagining other ways of life, other ways of viewing the world and talking about it, imagining unfamiliar places, meeting new people there and making new friends. However, as teachers and researchers, we know very little about how learners employ their imaginations to do any of these things nor do we know how to best utilize learners’ imaginations to facilitate their language learning. In this special issue of Studies in Second Language Learning and Teaching, we hope to highlight the growing scholarly interest in the role of imagination in foreign language learning and bring together diverse strands of research with a view to stimulating a future research agenda. Our own experiences as researchers and teachers have convinced us of the power of imagination in learning processes and it is our hope that this collection of papers will offer a forum for the sharing of ideas and promoting interest in what we believe to be a central aspect of the language learning experience.